Rei esquilo: relações entre antropocentrismo e ecocentrismo através de xilogravuras narrativas - Souto, Marcos Paulo Pinheiro (2018)
The research deals with a reflection on the relationship between ecocentrism and anthropocentrism through an artistic approach. Through a narrative with fictional elements have been made woodcuts that focus on the construction of a humanoid character and the relationship with the nature that surrounds him. Using the theoretical basis of Ecosophy from Guattari and starting from the artist's own experience throughout this research process, the narrative serves as a background to discuss questions about the co-relation between wild nature and human nature, between eccentric and anthropocentric modes of thought and the necessary paradigm shift in the current human relationship with the environment.